Analysis Of Product Quality In Manisan Sumatra, Medan - zhang, susanto (Adpebi Science Series, 2022)
Abstract The purpose of this research is to determine the quality of the product in Manisan Sumatra, Medan. The method used in this research is descriptive qualitative research method. The data collection method used by the author in this study is through the interview method. Data obtained from interviews using source triangulation, where the informants in this study were 5 customers in Manisan Sumatra, Medan. The data of this study were analyzed using the data analysis method proposed by Miles & Huberman, namely: Data Reduction, Data Display, and Conclusion Drawing. In this study, the authors found several findings, such as customers still not satisfied with the quality of the taste of the product served by Manisan Sumatra, Medan because the taste of the product is inconsistent, and the appearance of the product is considered less attractive for customers to buy, such as the packaging used is less attractive.